Aspirin reduces the mortality risk of sepsis-associated acute kidney injury: an observational study using the MIMIC IV database - Chen, Sining; Li, Shishi; Kuang, Chaoying; Zhong, Yuzhen; Yang, Zhiqian; Yang, Yan; Liu, Fanna (Frontiers in Pharmacology, 2023)
Sepsis-associated acute kidney injury (SA-AKI) is a complication of sepsis and is characterized by high mortality. Aspirin affects cyclooxygenases which play a significant role in inflammation, hemostasis, and immunological regulation. Sepsis is an uncontrolled inflammatory and procoagulant response to a pathogen, but aspirin can inhibit platelet function to attenuate the inflammatory response, thus improving outcomes. Several studies have generated contradictory evidence regarding the effect of aspirin on patients with sepsis-associated acute kidney injury (SA-AKI). We conducted an analysis of the MIMIC IV database to investigate the correlation between aspirin utilization and the outcomes of patients with SA-AKI, as well as to determine the most effective dosage for aspirin therapy.SA-AKI patients' clinical data were extracted from MIMIC-IV2.1. Propensity score matching was applied to balance the baseline characteristics between the aspirin group and the non-user group.Subsequently, the relationship between aspirin and patient death was analyzed by Kaplan-Meier method and Cox proportional hazard regression models.12,091 patients with SA-AKI were extracted from the MIMIC IV database. In the propensity scorematched sample of 7,694 individuals, lower 90-day mortality risks were observed in the aspirin group compared to the non-users group (adjusted HR: 0.722; 95%CI: 0.666, 0.783) by multivariable cox proportional hazards analysis. In addition, the Kaplan-Meier survival curves indicated a superior 90-day survival rate for aspirin users compared to non-users(the log-rank test p-value was 0.001). And the median survival time of patients receiving aspirin treatment was significantly longer than those not receiving (46.47 days vs 24.26 days). In the aspirin group, the average ICU stay length was shorter than non-users group. (5.19 days vs 5.58 days, p = 0.006). There was no significant association between aspirin and an increased risk of gastrointestinal hemorrhage (p = 0.144).Aspirin might reduce the average ICU stay duration and the 30-day or 90-day mortality risks of SA-AKI patients. No statistically significant difference in the risk of gastrointestinal hemorrhage was found between the aspirin group and the control group.